THE CREDIT RISK, OPERATIONAL RISK AND FINANCIAL PERFORMANCE OF BANKING COMPANIES LISTED ON INDONESIA STOCK EXCHANGE - Muliana Muliana (POINT: Jurnal Ekonomi dan Manajemen, 2019)
This study aims to analyze the effect of credit risk and operational risk on the financial performance of banking companies, both partially and simultaneously. The data used in this study are secondary data sourced from financial statements of banking companies (Conventional Banks) of 8 companies during the 2014-2018 period. Data analyze using Multiple Linear Regression. The results showed that partially the t value of credit risk (NPL) was greater than the value of Financial Performance (ROA) and a significant value of 0.080> 0.05 means that credit risk had no significant effect on financial performance. The t value of operational risk (BOPO) is greater than the profitability value and a significant value of 0.003 <0.05 means that Operational risk has a significant effect on financial performance (ROA). Simultaneously, credit risk and operational risk significantly influence financial performance (f table 3.25 (4.963> 3.25) and sig value 0.012 <0.05)